Wiley acing GATE: mechanical engineering - Tamrakar, Ajay Kumar (Wiley, 2014)
Wiley acing GATE: mechanical engineering / Tamrakar, Ajay Kumar. -- New Delhi: Wiley, 2014 153.94621 T153 No. of Copies : 1